IMMUNE STATE OF THE CHILDREN WITH BRONCHIAL ASTHMA FROM THE AMUR RIVER AND YAKUTIA REGIONS - M. V. Efimenko; M. I. Samsonova; E. N. Suprun; T. E. Burtseva; L. E. Nikolaeva; V. K. Kozlov (Медицинская иммунология, 2014)
Abstract. This work presents data on immune state of children with bronchial asthma living under environmental conditions of the Yakutia and Amur river regions. We examined immune functions of blood cells in 102 children with allergic diseases (bronchial asthma). Certain geographical and ecological conditions provide some specific change of immune system (immune deficiency) in the children with allergy. We have shown that the children with bronchial asthma exhibited immunological shifts in Th1/Th2 mechanism of immune responses, enhancement of humoral immune factors and deficiency of the phagocyte components.